Evaluating The Effectiveness of The PMTCT Program at RSUD Jayapura: A Mixed Method Study - Lestari, Muji; Wahyuni, Sri (JURNAL KEBIDANAN, 2024)
At RSUD Jayapura, from 2021 to 2023, 62 babies were born to HIV-positive mothers. However, no prior study has evaluated whether all these babies were tested for HIV. Babies born directly into the delivery room without passing through the VCT clinic often face challenges in follow-up, especially with high dropout rates in the Prevention of Mother-To-Child HIV Transmission (PMTCT) program.Â  This study aimed to evaluate HIV transmission in babies enrolled in the PMTCT program at RSUD Jayapura and assess the involvement of healthcare providers (doctors, midwives, nurses, counselors, and lab technicians) in the program. A mixed-methods approach was used, combining quantitative (case-control design) and qualitative (content analysis of in-depth interviews). The quantitative sample included 64 babies born to HIV-positive mothers who participated in the PMTCT program from 2021 to 2023. The qualitative sample comprised 5 healthcare providers involved in the program. Data were analyzed using Chi-Square tests for quantitative analysis and content analysis for qualitative data. Chi-Square analysis showed a significant association with a p-value of 0.00 (<0.05) and an Odds Ratio (OR) of 217.000, indicating a strong impact of the PMTCT program in preventing HIV transmission. In-depth interviews with the VCT head revealed many cases were lost to follow-up, especially those whose families moved out of the city. Babies who remained in the area were mostly HIV-negative by 18 months. Interviews with midwives highlighted that HIV-positive mothers with low viral loads typically delivered via caesarean section, though they faced delayed wound healing and higher infection risks. No discrimination was observed in room usage for HIV-positive mothers.